Electrochemical Response for Spherical and Rod Shaped WO3 Nanoparticles. (23rd October 2013) - Adhikari, Sangeeta; Sarkar, Debasish
Abstract : A rapid and new technique describes synthesis technique of spherical and rod shaped tungsten trioxide (WO3 ) nanoparticles with similar band gap at visible wavelength. Acid catalyzed exothermic reaction and structure directing reagent follows the formation of two different morphologies and monoclinic WO3 phase. Rod shaped WO3 nanoparticle coated ITO glass electrode exhibits high current density at identical low voltage and scan rate due to its better adherence and coating uniformity in comparison with spherical nanoparticles. WO3 -ITO electrode alters to blue tungsten bronze in color at low voltage, and further the color restores after removing the same applied voltage.